Mitigasi Biopiracy dan Kekayaan Intelektual : Tantangan dan Peluang Bagi Pengetahuan Tradisional - Dhimas Widyananda (Syntax Corporation Indonesia, 2024)
Indonesia, as a country with high biodiversity, is vulnerable to biopiracy. In response, Indonesia ratified the Convention on Biological Diversity which introduced the concept of Access and Benefit Sharing (ABS) to genetic resources and traditional knowledge that contain high economic value. This paper explains the mitigation of biopiracy against genetic resources and traditional knowledge with bioprospection so that it can be utilized sustainably for the greatest prosperity of the people. This paper is a normative legal research that uses legislative and conceptual approaches which will later elaborate whether genetic resources and traditional knowledge have received sufficient mitigation efforts from the threat of biopiracy, as well as bioprospection actions to improve the welfare of people who depend on genetic resources and traditional knowledge with sustainable technological development and innovation.